2020
DOI: 10.1186/s13033-020-00380-9
|View full text |Cite
|
Sign up to set email alerts
|

An explanatory model of factors enabling sustainability of let’s talk in an adult mental health service: a participatory case study

Abstract: Background: While effective interventions have been developed to support families where a parent has a mental illness in Adult Mental Health Services, embedding and sustaining them is challenging resulting in families not having access to support. This study developed an explanatory model of influencers that had enabled sustainability of the Let's Talk intervention in one service. Methods: A participatory case study was used to build an explanatory model of sustainability at the service using theoretical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 74 publications
(135 reference statements)
0
16
0
Order By: Relevance
“…Secondly, even though AMHS may appear the most natural fit for FT/FFP and provide a common context for the implementation of FFPs (45,48,49), families in this study reported benefits across both AMHS and CAMHS settings. FT is typically delivered as a preventive intervention to families whose children do not attend mental health services (14,15) but in this study, most of the child participants, including those who attended CAMHS, reported that FT had improved their well-being and family relationships.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Secondly, even though AMHS may appear the most natural fit for FT/FFP and provide a common context for the implementation of FFPs (45,48,49), families in this study reported benefits across both AMHS and CAMHS settings. FT is typically delivered as a preventive intervention to families whose children do not attend mental health services (14,15) but in this study, most of the child participants, including those who attended CAMHS, reported that FT had improved their well-being and family relationships.…”
Section: Discussionmentioning
confidence: 75%
“…As noted in previous qualitative studies, they felt that this had enabled all perspectives to be surfaced and heard, and improved mutual understanding and family relationships ( 32 34 ). Nevertheless, whole-family programmes appear to be less commonly delivered than parent-only models ( 48 , 49 ), most probably due to the additional buy-in and logistics required in involving children. Our findings suggest that without the involvement of the child(ren), parents may not become aware of their worries and burdens as demonstrated here by the surprise and alarm that parents reported when their children opened up during the FT sessions.…”
Section: Resultsmentioning
confidence: 99%
“…The model is drawn from a series of five mixed method studies exploring the sustainability of the family-focused practice, Let's Talk about Children (LTC) in eight AMHS in Victoria, Australia, involved in a RCT of LTC ( 52 ). The series of studies documented practitioner use and organizational capacity in the eight AMHS and developed an explanatory model of factors enabling sustainability in one AMHS ( 45 , 66 – 69 ). The research series used a participatory research approach working in partnership with change agents within AMHS across Victoria.…”
Section: Design and Methodsmentioning
confidence: 99%
“…However, this type of service delivery is not as common in services who might be coming into contact with these parents and their families (15). In adult mental health, for example, a change to this type of service delivery is slow, as it is in conflict with the predominant medicalised individual client care model, and enhanced by limiting supportive administrative structures to encourage family focused practice (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%